CLINICAL AND MICROBIOLOGICAL EVALUATION OF THE CONDITION OF PERIODONTAL TISSUES IN PATIENTS WITH CARDIOVASCULAR DISEASE - T. Timokhina; Akbari Sunus; Y. Kolenko (Bogomolets National Medical University, 2015)
Summary. 36 patients with cardiovascular disease were examined, namely, arterial hypertension and coronary heart disease. A total of 88,9 % of the examined had risk factors of osteoporosis. The study has showed that all patients with cardiovascular pathology are subject to some degree of periodontal tissue lesions, but most often was diagnosed generalized periodontitis III degree. All the patients with cardiovascular disease are needed to be searched for risk factors and clinical markers of osteoporosis. It is necessary to add antiosteoporotic therapy in complex treatment of periodontal diseases.